X-ray color maps of the zoned garnets from Silgará Formation metamorphic rocks,SantanderMassif, Eastern Cordillera (Colombia) - Takasu Akira; Castellanos A. Oscar Mauricio; Ríos R Carlos Alberto (Earth Sciences Research Journal)
The metamorphic rocks of the Lower Paleozoic Silgará Formation of the Santander Massif, Eastern Cordillera (Colombia), were affected by a Barrovian-type metamorphism under low to high temperature and medium pressure conditions. These rocks contain garnet porphyroblasts, which show several kinds of chemical zoning patterns. The garnet grains behave as closed systems with respect to the rock matrix. Most of the observed zoning patterns are due to gradual changes in physicochemical conditions during growth. However, some garnet grains show complex zoning patterns during multiple deformation and metamorphic events.